The Electoral Advantage of the Left in Times of Fiscal Adjustment - Abel Bojar (London School of Economics and Political Science (LSE), European Institute, 2016)
Despite widely held views on fiscal adjustment as a political minefield for incumbents, the empirical literature on the issue has been surprisingly inconclusive. A crucial variable that has been often overlooked in the debate is partisan politics. Building on the micro-logic of Albert Hirschman's "exit, voice and loyalty" framework, this article offers a novel theoretical perspective on the conditioning impact of partisanship in the electoral arena. Due to their more limited exit options at their disposal, left-wing voters are less likely to inflict electoral punishment on their parties, offering the latter an electoral advantage over their right-wing rivals. Relying on the largest cross-national dataset to date on the evolution of close to 100 parties' popularity rating in 21 democracies, time-series-cross-section results confirm this electoral advantage.
Keywords: 330; fiscal adjustment; partisan politics; exit voice and loyalty; party competition; elections; popularity